Analisis Pengaruh Total Pembiayaan dan Return on Asset (ROA) Terhadap Pertumbuhan Total Aset Bank Syariah di Indonesia Periode 2014-2018 - Risna, Risna (JYRS: Journal of Youth Research and Studies, 2020)
The growth of Islamic banks shows an increase from year to year. one of the factors supporting the growth of Islamic banks is the increasing trend of the halal industry or halal tourism which is supported and financed by Islamic banks. From the disbursed financing will generate profitability. The profitability measurement tool is ROA, which shows the ability of bank management to generate profits from assets owned. If profits increase, it will have a positive impact on the growth of total assets of Islamic banks.This research uses associative quantitative research, the data source in this study uses secondary data sources. The data analysis techniques in this study use descriptive statistics, classical assumption tests and hypothesis testing. The results of this study indicate that the total financing and ROA simultaneously have a significant effect on the growth of total assets of Islamic banks in Indonesia.